Development and simulation of new electrode designs for improved hydrogen production in alkaline electrolyzers - Ismail, Mohamed M.; Erdemir, Dogan; Dincer, Ibrahim (ELSEVIER, 2025)
This study develops multiple modified electrode surface geometries which aims at enhancing the hydrogen production rates of alkaline water electrolyzers (AWEs). Subsequently, the study investigates how the developed simulation model to determine is utilized to evaluate the flow characteristics and identify the optimal electrode surface modification. The model incorporates dimpled electrode surfaces with circular, triangular, and rectangular shapes. Furthermore, we study each dimple shape in its inward, outward, and alternating configurations. The simulations show that these surface modifications can introduce localized turbulence to the flow inside the gas evolution chamber. This, in turn, improves the gas bubbles' separation from the electrode surface. The results demonstrate a correlation between the induced turbulence from electrode surface changes and an increase in the volume fraction of evolved gases. Notably, inward-facing rectangular dimples lead to an increment in hydrogen volume fraction of up to 9.7%. This study highlights the critical role of electrode geometry in improving AWE performance and provides insights for advancing green hydrogen production technologies.
Keywords: Alkaline water electrolysis; CFD; Hydrogen; Hydrogen production; Electrode; Electrochemical modeling; Science & Technology - Other Topics; Energy & Fuels